Optical Devices in Communication and Computation - Xi, Peng (IntechOpen, 2012)
Optical devices in communication and computation have a significant impact on our daily life, although we may not even be aware of their existence, as in case of inter-continent fiber cables that connect people around the world, making it a global village. Novel nanoscale structures have demonstrated a wide range of unique features; therefore have became a hot research topic. Not only that the novel structural materials are used in biomedical therapy, but also the nature inspires the design of innovative optical structures. In this book, we focus on recent developments of theoretical analysis, designs of novel nano-photonic structures and functional materials for optical instrumentation. This book is constituted of 10 chapters contributed by renowned researchers from all over the world who work in the forefront of this field.